IMPLEMENTATION OF THE RESONANCE METHOD TO MEASURE THE SPEED OF SOUND USING PVC PIPES AND SMARTPHONE - Sulistya, Eko (Universitas negeri Yogyakarta, 2024)
The objective of this study is to replace the conventional approach that involved using water and vertically-held pipes in the measurement of sound speed. In this new method, the sound source is generated by an Android application called Tone Generator, utilizing a smartphone. The study investigates frequency variations in the range of 500 Hz to 1000 Hz with interval of 100 Hz. By graphing the length of the organ pipe against the harmonic number (n), where n is odd number, we observed a linear relationship. From this linear relationship, the speed of sound in the experimental setup was calculated. The speed of sound was determined to be 346 m/s with a standard deviation of 2 m/s, which is in close agreement with the reference speed of sound at 25 degrees Celsius. This innovative approach offers a convenient and accurate way to measure the speed of sound, making use of readily available smartphone applications and simplifying the experimental setup compared to traditional methods.